2022
DOI: 10.1007/s10140-022-02070-0
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of teleconsultation in the diagnosis and treatment of proximal humeral fractures

Abstract: Purpose Teleconsultation has become a routine part of clinical practice. The question arises as to whether this is reliable or not. Various studies have assessed the reliability in fractures at other locations in the extremities, but there is no study investigating teleconsultation reliability for proximal humeral fractures, proximal humerus fractures, which are fractures that may cause difficulties in making diagnosis and treatment decisions. Our aim was to evaluate whether proximal humerus fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Pamuk showed that orthopedists can safely perform tele consult using their own smartphone in the radiological evaluation of proximal humerus fractures. Although it will never replace a consult in person, this "smartphone approach" is highly reliable for diagnostic and treatment-related decision [16].…”
Section: Discussionmentioning
confidence: 99%
“…Pamuk showed that orthopedists can safely perform tele consult using their own smartphone in the radiological evaluation of proximal humerus fractures. Although it will never replace a consult in person, this "smartphone approach" is highly reliable for diagnostic and treatment-related decision [16].…”
Section: Discussionmentioning
confidence: 99%
“…The use of WhatsApp and other social media platforms by orthopaedic surgeons has been explored by Jildeh et al [ 25 ], who noted the advantages of such tools in enhancing patient-physician communication and disseminating accurate information. Studies by Pamuk[ 5 ] and Stahl et al [ 8 ] demonstrated the reliability of WhatsApp for teleconsultation and decision-making in orthopaedic trauma, respectively, with findings suggesting near-perfect agreement with traditional diagnostic methods. Further, Kapıcıoğlu et al [ 26 ] affirmed the safety and reliability of using WhatsApp for decision-making regarding paediatric supracondylar fractures, and Sumargono et al [ 27 ] reported high satisfaction rates with virtual clinics using WhatsApp for postoperative follow-up after total knee replacement surgery, emphasizing its potential continuity beyond the pandemic context.…”
Section: Evidences Of Whatsapp In Medical Care and Medical Teachingmentioning
confidence: 99%
“…The role of social media and mobile applications in clinical education has gained prominence, enriching the curriculum and empowering students with a wealth of knowledge and preparedness beyond traditional classroom settings[ 4 ]. Furthermore, the coronavirus disease 2019 (COVID-19) pandemic underscored the importance of teleconsultation services, necessitating adjustments in hospital workflows and highlighting the critical role of technology in maintaining continuity of care[ 5 ]. WhatsApp, in particular, has distinguished itself as a versatile tool for text and multimedia communication within the medical community[ 6 ].…”
Section: Introductionmentioning
confidence: 99%